POTENSI EKONOMIS TANAMAN AREN (Arenga pinnata) PETANI AREN DI DESA NAGA REJO KAB. DELI SERDANG SUMUT - Muhammad Nuh; Mahyu Danil; Wan Bahroni Jiwar Barus; Aprillawati Aprillawati; Miranti Miranti (Jurnal Pengabdian Mitra Masyarakat, 2021)
Palm trees are generally found growing wild (not planted by people). Palm trees are one of the natural resources in the tropics. Its distribution is widespread, indispensable, and easily available for daily needs by the local community as a sustainable resource. In Indonesia, most of the palm trees are actually used for building materials, baskets, handicrafts, roofs, sugar, candied fruit, and so on.Almost all parts of this tree can be utilized and have economic value starting from the physical parts of the tree as well as from its production results. Traditionally, people process palm sap into rock sugar (brown sugar) or ant sugar in the form of crystals, until now not touched by technological developments (more on culture).Many people are not aware of the high economic value produced by palm trees. In fact, in addition to having high economic value, sugar palm is suitable as a protective plant in watershed areas (DAS). The tree of the plant has fibrous roots and can withstand erosion. On the other hand, it is believed that palm trees will not be ogled by forest encroachers, because they cannot be used as wood, like other types of wood. Sugar palm farmers in Naga Rejo Village, Deli Serdang Regency, North Sumatra, in the sugar production process, use the main supporting material of polar extract of jackfruit wood as a preservative during the tapping process to obtain sap.  The results showed that the use of a polar extract of jackfruit wood 50 ml per liter of sap in the tapping process in addition to producing sap with better quality, also facilitated the processing into palm sugar. The palm sugar produced has a good texture, color, aroma, and distinctive taste of palm sugar (the best quality of palm sugar).